Surgical Management of Ascending Aortic Aneurysm and Its Complications - Sisira Sran; Manpreet Sran; Nicole Ferguson; Amgad N. Makaryus (Case Reports in Vascular Medicine)
Ascending aortic aneurysms involving the proximal aortic arch, arising anywhere from the aortic valve to the innominate artery, represent various problems in which open surgery is generally required. Surgical options include excision of the aortic pathology or wrapping the aneurysm shell with an aortic Dacron graft. Intervention using the latter method can lead to extravasation of blood along the suture lines resulting in continuous bleeding within the periprosthetic space. The Cabrol technique was developed as a method for decompression of postoperative leaks by the formation of a conduit system from the periprosthetic space to the right atrium. The coronary ostia are anastomosed to a second graft in an end-to-end fashion, which is then anastomosed to the ascending aortic conduit side to side. The native aorta is then sewn around the prosthesis, hereby creating a shunt to drain anastomotic leakage. This shunt reduces postsurgical risk of pseudoaneurysm formation and normally closes a few days following surgery. We discuss the case of a patient who underwent Cabrol’s variation and six months later was demonstrated to have a patent shunt.